FAKTOR YANG MEMPENGARUHI PROFITABILITY PADA PERUSAHAAN MANUFAKTUR YANG TERDAFTAR DI BEI - Irene Josephine; Elizabeth Sugiarto Dermawan (Fakultas Ekonomi, Universitas Tarumanagara, 2022)
This research was conducted aims to obtain empirical evidence about firm size, inventory turnover, working capital efficiency, and total sales growth that affect the profitability of companies in the manufacture companies that listed in Indonesian Stock Exchange 2017 to 2019. Samples was selecting using purposive sampling method and the valid data was 241 data. Data processing techniques using multiple regression analysis what helped by SPSS program (Statistical Product and Service Solution) for windows released 24 and Microsoft Excel 2007. 7The result of this study inidicate that the firm size and total sales growth have a positive significant effect on profitability, working capital efficiency have a negative significant effect on profitability, inventory turnover does not have a significant effect on the profitability. The implication of this study is the need to increase total sales, inventory, firm size and working capital toincrease profitability which will bring a good signal for investor.